1983
DOI: 10.1007/bf00502624
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of central dopamine receptors in the hypotensive action of pergolide

Abstract: The involvement of central dopamine receptors in the hypotensive action of the dopaminergic ergoline, pergolide was determined in anesthetized rats. Intravenous (i.v.) or intracerebroventricular (i.v.t.) administration of pergolide (12.5, 25 and 50 micrograms/kg) produced dose-dependent decreases in blood pressure. The magnitude of hypotension seen following either i.v. or i.v.t. administration of pergolide was similar. However, while both sulpiride (1 mg/kg, i.v.) as well as phentolamine (1 mg/kg, i.v.) antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Indeed, it has been reported that dopamine receptor agonists may cause orthostatic hypotension and subjective dizziness [8–12, 14, 46]. This propensity of these drugs is consistent with a reduction in sympathetic activity which may be caused by central [47, 49, 50] and/or peripheral [51–53] mechanisms. Although the location of the central dopamine receptors mediating the sympatholytic effect of dopamine receptor agonists has not been established, it is likely that the VTA is involved since there is evidence that activation of the VTA results in an increase in BP in experimental animals [54].…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, it has been reported that dopamine receptor agonists may cause orthostatic hypotension and subjective dizziness [8–12, 14, 46]. This propensity of these drugs is consistent with a reduction in sympathetic activity which may be caused by central [47, 49, 50] and/or peripheral [51–53] mechanisms. Although the location of the central dopamine receptors mediating the sympatholytic effect of dopamine receptor agonists has not been established, it is likely that the VTA is involved since there is evidence that activation of the VTA results in an increase in BP in experimental animals [54].…”
Section: Discussionmentioning
confidence: 77%
“…The increased MHPG sulfate/norepinephrine concentration ratio suggests norepinephrine release may be increased as well. Whether these neurochemical changes are related to functional effects of dopamine agonists such as decreased blood pressure (Jadhav et al, 1983) and increased serum corticosterone concentration is presently unknown, but there have been suggestions that epinephrine neurons can modulate both blood pressure (Saavedra et al, 1976) and corticotrophin-releasing factor secretion (Mez~ et al, 1984) in rats.…”
Section: Discussionmentioning
confidence: 97%